State participation in business concerns in Italy - COSMO, G. (PSL Quarterly Review, 2014)
The article outlines the present-day situation of State participation in business concerns in Italy in its complicated pattern and in its significance for the several branches of the national economy. Special attention is devoted to the problems of the Istituto per la Ricostruzione Industriale (Industrial Reconstruction Institute) which holds a central position in the field of State participation in business concerns, and to certain critical regional situations which make it difficult to adopt rational and comprehensive solutions. A general reorganisation of the so-called partecipazioni economiche dello Stato is however an urgent need in Italy, and has been the subject of a special Government enquiry but which until now has led to no results. JEL: H11, H50